RATIONALE FOR A COURSE IN QUANTITATIVE METHODS. - Singer, Frank A. (The Accounting Review, 1962)
Abstract It has become an objective of some of the members of the faculty at the University of Massachusetts to deal with all the subject matter offered in the School of Business Administration as the philosophy, information and skill necessary and appropriate to the general problem of administration. In order to maintain and communicate this focus it is necessary to organize classes around more fundamental subject classifications. These classifications are in terms of what managers need to be able to do rather than in terms of the responsibilities and activities of persons who occupy particular niches in an organization chart. One of the problems which this approach creates is a greater difficulty in conveying to a student the relevance of a particular course to his educational objectives. It was relatively simple to explain that there is some one called a sales manager, or controller, or treasurer whose shoes one day he might fill. Since not all business problems are amenable to a quantitative analysis, and since very many different kinds of problems are amenable, it is useful in an introductory way to examine the functions which numbers can perform.